Detecting Unknown Persons Using Surveillance Camera: A Recent Study - P. C. Karthik (Technological Innovation in Engineering Research Vol. 4, 2022)
Security refers to a condition in which products, creatures, or individuals are given unique identification and the ability to move data over a network without relying on human-to-human or human-to-PC collaboration. The webcam was created as a result of the convergence of remote advances and the Internet. The security framework is the connection of something with anything else, typically the movement of useful information, such as a sensor in a location that monitors and controls temperature. To show a security alert system that uses low-power chips and the Internet of Things to help with checking and receiving alerts when movement is detected, as well as sending the data to an approved individual. Furthermore, an Internet of Things-based application can be used remotely to monitor activity and get notifications when movement is detected. Hence, focal points like these make this application perfect for checking homes in nonappearance.